EP-519 A Bit of a Headache: Management of Head Injuries in a District General Hospital. (9th August 2022) - Bruce, Nikki; Young, Jamie
Abstract: Aim: Head Injury is a common presentation in our DGH, which covers a large rural area and is now a regional trauma centre. We audited our management of head injuries against current guidelines and planned a new pathway to ensure patients receive the correct advice and follow up on discharge. Method: Data was requested from IT for all head injury episodes in 2019, to reflect usual numbers pre-pandemic. Electronic letters, radiology and notes were used to identify whether imaging criteria was met/carried out, discharge destinations, re-presentations, specialty discussions, and head injury advice on discharge. Results: 307 individual patients identified. 13 re-presentations. 10 required neurosurgical discussions. Destinations: 226 (73.6%) discharged direct from ED. Admissions; Surgical - 37 (12%), Medical - 6 (2%), Paeds – 14 (4.5%), ITU 2 (0.7%), Did not wait – 2 (0.7%), Not Recorded – 7 (2.3%). Imaging: 100 patients met NICE criteria for CT, 100% were documented in notes and had CT. 76% reported normal, 18% had a bleed, contusion or haematoma. HI advice 90% of ED discharges, 16% of Surgical and 16% of Medical discharges had head injury discharge advice documented. Conclusions: Guidelines were met for 100% of patients requiring imaging Head injury advice was well documented in ED but fell down in ward paperwork. We have written a robust pathway where all inpatients have a proforma completed during admission with prompts for discharge advice and rehab referral where appropriate, this is currently undergoing a re-audit to ensure improvement and if successful will become an established part of the trauma pathway in our hospital.